Rasio Keuangan Sebagai Variabel Prediktor Harga Saham Pada Perusahaan Pertambangan Batu Bara - Uun Malihan Hawa (Politeknik Ganesha Medan, 2023)
Coal stocks are stocks that have been the target of investors in recent times because the price has reached its highest peak in the last ten years. This study aims to determine the effect of the variables Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Gross Profit Margin (GPM), and Earnings Per Share (EPS) which also involve the growth of total assets as a control variable on stock prices, both partially and simultaneously at the coal mining companies ADRO, ITMG, and PTBA. The method used in this research is quantitative analysis with panel data regression. The data used is from 2010-2020 and involves three companies so the total observations are 30 company years. The results show that ROA, ROE, and GPM have an effect on stock prices, while DER and EPS growth have no statistically significant effect.